Do Different Hurdle Heights Alter Important Spatiotemporal Variables in Hurdle Clearance? - Ozaki, Yusuke; Ueda, Takeshi (Frontiers in Sports and Active Living, 2022)
This study aimed to determine whether important spatiotemporal variables in hurdle clearance change with different hurdle heights. Twelve male hurdlers (mean height, 1.75±0.04 m) cleared hurdles set at different heights (10% higher [High] and 10% lower [Low] than the centre of mass [CM]); images were captured by six high-speed cameras, and each spatiotemporal variable was calculated. Thereafter, the difference in each spatiotemporal variable between High and Low and the relationship between the mean horizontal velocity from takeoff to landing (HC-v) and each spatiotemporal variable were examined. Our findings indicated that values for flight time, flight time from hurdle to landing (2nd flight time), clearance time, release height on takeoff, peak height of the CM, and the difference in landing distance were greater in the High condition than in the Low condition. Moreover, a low rate of deceleration on takeoff and short 2nd flight time, clearance distance, and takeoff distance were more strongly related to HC-v in the condition High, whereas a low rate of deceleration on landing, short flight time from takeoff to hurdle (1st flight time), high release height on landing, and touchdown height on landing were more strongly related to HC-v in the Low condition. Therefore, coaches should consider these changes in spatiotemporal variables when changing hurdle heights based on age group or event. It should also be noted that, even when the hurdle heights are the same, the spatiotemporal variables that should be considered may differ depending on the height of the hurdler.